Managing Consumer Loyalty through Acquisition, Retention and Experience Efforts: An Empirical Study on Service Consumers in India. (June 2016) - Singh, Jagwinder; Saini, Shivani
Recent developments in the marketing literature highlight the significance of consumer relationship management (CRM) in driving consumer loyalty (CL). In order to provide a clear understanding about the impact of CRM on CL, this study develops an integrated framework of CRM activities: acquisition, retention and experience to manage CL through direct and indirect approaches (with mediation of satisfaction, trust and commitment). The article utilizes a survey-based empirical study of 600 consumers from three service sectors (health, retail and wellness). Subsequently, structural equation modelling through multiple group analysis has been used to test a series of hypotheses concerning the direct as well as indirect effects of consumer relationship efforts on CL. The findings of the study suggest that a firm that pays more attention to manage consumer experiences would be significantly benefited from the implementation of CRM programmes. Consumer experience efforts have the positive impact on CL through commitment in all three sectors. The acquisition efforts are sufficient enough to develop partial CL through satisfaction in health and wellness services only. Similarly, retention efforts manage to develop CL partially by satisfaction and trust in all three select services. Among the three proposed mediators, only commitment drives true CL.